Medical Imaging 2018: Biomedical Applications in Molecular, Structural, and Functional Imaging 2018
DOI: 10.1117/12.2293603
|View full text |Cite
|
Sign up to set email alerts
|

Automatic quantification framework to detect cracks in teeth

Abstract: Studies show that cracked teeth are the third most common cause for tooth loss in industrialized countries. If detected early and accurately, patients can retain their teeth for a longer time. Most cracks are not detected early because of the discontinuous symptoms and lack of good diagnostic tools. Currently used imaging modalities like Cone Beam Computed Tomography (CBCT) and intraoral radiography often have low sensitivity and do not show cracks clearly. This paper introduces a novel method that can detect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…15 Early detection plays an important role in the diagnosis of a crack, which could significantly limit further growth of the crack and save the tooth. 10,13 In our previous pilot studies, we demonstrated the feasibility of ICG-NIRF dental imaging based on both a rat model 40,41,44 and human extracted teeth. 42,43 These results showed the promise of using ICG-NIRF dental imaging for crack detection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15 Early detection plays an important role in the diagnosis of a crack, which could significantly limit further growth of the crack and save the tooth. 10,13 In our previous pilot studies, we demonstrated the feasibility of ICG-NIRF dental imaging based on both a rat model 40,41,44 and human extracted teeth. 42,43 These results showed the promise of using ICG-NIRF dental imaging for crack detection.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to image cracks by dental X-ray/CT makes tooth cracks one of the most notoriously difficult dental diseases to be diagnosed at an early stage, even for an experienced dentist, 1,13 which greatly limits the treatment of cracks. 10 Even for severe cracks that extend into both dentin and enamel, the enamel portion of cracks remains unidentifiable in dental X-ray and CT slices. Although existing studies suggest that CBCT could improve the diagnostic accuracy of tooth cracks 10 or that microCT provides even better dental resolution, 23 the cracks were not detectable even with the high resolution of microCT in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the wavelets fulfill the conditions from Proposition 2. 3. The mother wavelets are represented at i = 0…”
Section: List Of Figuresmentioning
confidence: 99%